Enhancing the Use of ChatGPT for Self-Talk Practice: Integrating Gamification and Artificial Intelligence into Arabic Language Education - Muhammad Hafidz; Amrini Shofiyani; Muhammad Yasin Fatchul Barry (Journal of Educational Studies, 2025)
Conversation skills often pose a major obstacle for self-directed learners of Arabic due to the limited availability of conversation partners and authentic practice environments. The emergence of artificial intelligence, such as ChatGPT, presents new opportunities; however, its use for conversational practice remains suboptimal due to the absence of structured pedagogical approaches, including gamification elements that could enhance motivation. The main research question is: How can the use of ChatGPT as a virtual conversation partner for self-directed conversational practice be improved by integrating principles of gamification and artificial intelligence to effectively enhance Arabic speaking skills?. This research aims to: (1) design a model for self-directed conversational practice based on ChatGPT and integrated with gamification elements (points, levels, challenges, immediate feedback); (2) test the effectiveness of this model in improving speaking fluency, vocabulary mastery, and learner self-confidence; (3) identify the strengths and limitations of ChatGPT as a conversational agent in the context of Arabic language teaching. The research adopts a design-based research methodology and consists of three phases: needs analysis, model development, and a limited-scale experiment. Participants are 30 self-directed learners of Arabic at the basic and intermediate levels. Instruments include oral tests (pre- and post-), an observation form for interactions with ChatGPT, a motivation questionnaire, and semi-structured interviews. Quantitative data will be analyzed using paired-samples t-tests, while qualitative data will be analyzed using thematic analysis. The research is expected to provide: (1) a structured protocol for self-directed conversational practice using ChatGPT with gamified scenarios (e.g., daily tasks, conversation challenges, a point system); (2) empirical evidence of significant improvement in speaking fluency (with a minimum target of 25%) and learning motivation compared to traditional methods; (3) practical recommendations on how to formulate effective prompts for ChatGPT to generate responses appropriate to learners' proficiency levels and to support topic-based conversational practice. Optimizing the use of ChatGPT for self-directed conversational practice requires pedagogical design that not only relies on AI capabilities alone but also incorporates gamification principles to maintain engagement and sustainability in learning. The findings of this research are expected to serve as a reference for developers of Arabic teaching materials and for self-directed learners in using AI effectively. Further research is recommended to test this model over a longer period and with a broader population